2013
DOI: 10.1055/s-0033-1347255
|View full text |Cite
|
Sign up to set email alerts
|

Tattoos und Piercings: Motive für Körpermodifi­kationen bei Frauen mit Borderline-Symptomatik

Abstract: Do women suffering from borderline symptomatology differ from women without these symptoms regarding their motives for body modifications?A sample of 289 women with body modifications were questioned about their tattoos, piercings and motives for body modifications as well as about symptoms of borderline personality disorder. Women with borderline symptomatology were compared to women without borderline symptomatology concerning the extent of and motives for body modification.The 2 groups showed no differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
(30 reference statements)
1
11
1
Order By: Relevance
“…In a more recent international study, Kluger et al (2019) evaluated the prevalence of tattooing among a representative sample of the population of 5 major countries ( n = 11 079) and found that, in the 25–34 years old subgroup (which can be compared in term of age to our sample), 27.3% of the sample had at least one tattoo (with 16.4% wearing one tattoo and 10.9% wearing several) which is far less than in our sample where 69.83% of BPD patients had at least one tattoo and 22.41% had more than 10% of their body covered. Concerning studies directly comparing BPD patients and the general population, only a few have been made, with conflicting results regarding this outcome (some finding a difference [ 42 ] and some not [ 43 ]). Given the lack of studies comparing body modifications in BPD patients with other clinical population, we also compared BM prevalence in BPD patients with BM prevalence in an adult ADHD clinical control group.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent international study, Kluger et al (2019) evaluated the prevalence of tattooing among a representative sample of the population of 5 major countries ( n = 11 079) and found that, in the 25–34 years old subgroup (which can be compared in term of age to our sample), 27.3% of the sample had at least one tattoo (with 16.4% wearing one tattoo and 10.9% wearing several) which is far less than in our sample where 69.83% of BPD patients had at least one tattoo and 22.41% had more than 10% of their body covered. Concerning studies directly comparing BPD patients and the general population, only a few have been made, with conflicting results regarding this outcome (some finding a difference [ 42 ] and some not [ 43 ]). Given the lack of studies comparing body modifications in BPD patients with other clinical population, we also compared BM prevalence in BPD patients with BM prevalence in an adult ADHD clinical control group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, borderline patients use tattoos to cope with negative life experiences, indicating that the tattoos help them to regulate negative emotions and inner tension. Furthermore, they reported that their tattoos remind them of identity-forming life experiences and thus represent reassurance (Höhner et al 2014). Indeed, Haubl (2000) considers identity formation to be the central motivation for getting a tattoo.…”
Section: Autobiographical Memory Memory Objects and Tattoosmentioning
confidence: 99%
“…An additional study by Hohner and colleagues (14) examined the link between the presence of borderline personality traits and body modification. In a sample of 289 women with body modifications, a group manifesting borderline personality traits was identified and then compared with the remaining women who did not manifest these same personality traits.…”
Section: A Change?mentioning
confidence: 99%
“…No difference was found in the number or nature of body modifications between the two groups. While a definitive conclusion on the relation between borderline personality disorder and body modification awaits more rigorously designed studies, the work of Hohner and colleagues (14) highlights that the number and type of body modification were not useful discriminators in a modern cohort of women. When compared with the work of Inch and Huws (12), the evidence presented by Hohner and colleagues also suggests that a re-evaluation of previously held assumptions about body modification and personality may be topical.…”
Section: A Change?mentioning
confidence: 99%